Characterization of the host specificity of the SH3 cell wall binding domain of the staphylococcal phage 88 endolysin - Tham, Hong Yun; Chong, Li Chuin; Krishnan, Melvina; Mohammad Khan, Asif; Choi, Sy Bing; Tamura, Takashi; Yusoff, Khatijah; Tan, Geok Hun; Song, Adelene Ai-Lian (Springer Science and Business Media Deutschland GmbH, 2025)
Bacteriophages produce endolysins at the end of the lytic cycle, which are crucial for lysing the host cells and releasing virion progeny. This lytic feature allows endolysins to act as effective antimicrobial alternatives when applied exogenously. Staphylococcal endolysins typically possess a modular structure with one or two enzymatically active N-terminal domains (EADs) and a C-terminal cell wall binding domain (CBD). The EADs degrade the peptidoglycan layer, leading to bacterial lysis, while the CBD binds to the specific host cell wall, and therefore, influences specificity of the endolysin. This study aimed to alter and characterize the host specificity of the CBD by exploring the impact of amino acid modifications within the CBD of a staphylococcal endolysin, Endo88. Endo88 was able to lyse Staphylococcus spp. and Enterococcus faecalis. However, despite attempts to mutate amino acids hypothesized for binding with cell wall components, the host-range was not affected but the lytic activity was severely reduced instead, although no alterations were performed on the EADs (Cysteine, histidine-dependent aminohydrolases/peptidases domain and Amidase domain). Further investigations of the CBD alone (Src homology3 domain, SH3) without the EADs suggested that binding and lytic activity may not be correlated in some cases since Endo88 and its mutants could lyse Staphylococcus epidermidis well but no binding activity was observed in the flow cytometry analysis. Molecular docking was used to gain insights on the observations for the binding and lytic activity which may help future strategies in designing enhanced engineered endolysins.